Pests and Fungal Organisms Identified on Olives (Olea europaea) in Florida - Jennifer L. Gillett-Kaufman; Sandra A. Allan; Jonael H. Bosques-Mendez; Lyle J. Buss (EDIS)
Olive production in Florida has increased over the last few years. As trees become available in nurseries many homeowners are planting them in their landscapes. Fortunately, olives are a relatively pest-free species, but some occasional invaders can be a nuisance or cause lasting harm. A few plant pathogens that may infect olives also can lead to a decline in overall plant health, fruit yield, or the visual appearance of plants. Following correct cultural practices when growing olives can reduce your chances of tree loss from pests and diseases. A survey of olive production and interviews with Florida growers in 2014 identified the pests and diseases described in this 5-page fact sheet, written by Jennifer L. Gillett-Kaufman, Sandra A. Allan, Jonael H. Bosques-Mendez, and Lyle J. Buss, and published by the UF Department of Entomology and Nematology, September 2014.